CULTURAL PROBLEMS IN TRANSLATION (Лучшие интеллектуальные исследования, 2025)
Abstract: Translation is not merely the transference of words from one language to another but an complicated  cultural process that encompasses worldviews, traditions, and unique ways of expression. Cultural problems in translation arise when concepts rooted in one cultural context lack equivalents in another. These challenges are further exacerbated by idiomatic expressions, historical references, and sociolinguistic norms that define one culture but remain foreign to another. This article explores the nature of these cultural difficulties, emphasizing how they affect meaning, tone, and intention in translation. Drawing on real-world examples and theoretical frameworks, it examines how translators navigate the cultural fields  of both linguistic and contextual directions.